Growing goats of different sexes have distinct metabolic responses to continuous feed restriction - Silva, Nhayandra C. D. [UNESP]; Härter, Carla J. [UNESP]; Figueiredo, Fernanda O. M. [UNESP]; Leite, Rafael F. [UNESP]; Neto, José M. Santos [UNESP]; Negrão, João A.; Teixeira, Izabelle A. M. A. [UNESP]; Resende, Kléber T. [UNESP] (CSIRO Publishing, 2018)
The objective of the present study was to investigate the effect of sex on the hormonal and metabolic changes in growing goats subjected to levels of feed restriction. We used 72 Saanen kids, including 24 intact males, 24 castrated males and 24 females with initial bodyweight of 15.76 ± 0.174 kg and initial age of 108.4 ± 18.86 days respectively. A split-plot design was employed (3 sexes ≤ intact males, castrated males, and females; 3 levels of feed restriction ≤ 0% (ad libitum), 25% and 50%). Groups of three goat kids were formed by sex (each goat eating one level of feed restriction); goats of each group were slaughtered when animals fed ad libitum reached 30 kg bodyweight. Fat and protein deposition were calculated by the difference between the determinations performed on samples of homogenates of control animals slaughtered at the start of the experiment and the experimental animals. Blood samples were collected every 10 days to evaluate glucose, total protein, albumin, urea, creatinine, cholesterol, non-esterified fatty acid, β-hydroxybutyrate, aspartate aminotransferase, gamma glutamyltransferase, creatine kinase, triiodothyronine (T3), thyroxine and insulin-like growth factor. Females presented greater fat deposition than did castrated and intact males, regardless of feed restriction (P < 0.0001). Protein body retention (kg) was affected only by feed restriction (P < 0.0001). In females, aspartate aminotransferase activity was greater in those subjected to 50% feed restriction (83.83 ± 4.96 U/L). Regardless of sex, the greatest serum β-hydroxybutyrate concentration was observed when animals were subjected to 50% feed restriction (P < 0.0149). Plasma concentration of insulin-like growth factor 1 was similar in castrated and females, being lower than in intact males. Intact males showed lower plasma T3 concentration than did females (P < 0.05). Females changed their glycolytic metabolism to retain fat deposition even under feed restriction, whereas males mainly changed their protein metabolism to retain protein synthesis, and were less affected by feed restriction.
Keywords: blood metabolites; castrated; energy; females; males; metabolism.